Chronic ill health in a regional Victoria setting: A 13‐year comparison. (25th October 2019) - Glenister, Kristen; Bourke, Lisa; Terry, Daniel; Simmons, David
Abstract: Objective: High‐quality data regarding the prevalence of chronic disease in rural areas are essential in understanding the challenges faced by rural populations and for informing strategies to address health care needs. This study compared the prevalence of a range of self‐reported chronic conditions and utilisation of GP services and emergency department in a regional Victorian setting between two studies conducted in the same region in 2001‐2003 and 2014. Design: Repeat cross‐sectional studies conducted over a decade apart. Setting: The projects were conducted in the Goulburn Valley in regional Victoria. Participants: The earlier study randomly selected households from local government lists. The later study randomly selected householders from the telephone directory. Main outcome measures: Participants were asked whether they had been diagnosed with a range of chronic health conditions and how often they had visited a general practitioner or emergency department in the past 12 months. Results: The age‐standardised prevalence of depression was higher in the 2014 study than the 2001‐2003 study in men (increased by 8.0% (95% CI 4.5, 11.5%)) and women (increased by 13.7% (95% CI 8.4, 19.0%)). Similarly, the prevalence of age‐standardised diabetes and hypertension was higher in 2014 than 2001‐2003 (men increased by 3.6% (95% CI 0.7, 6.5% (diabetes)) and 13.6% (95% CI 8.6, 18.6% (hypertension)), women increased by 3.1% (95% CI 0.3, 6.5% (diabetes)) and 8.4% (95% CI 2.3, 14.5% (hypertension))). Conclusion: The results of this study indicate that the prevalence of self‐reported depression, diabetes and hypertension has increased in this regional Victorian area over the past 13 years. The reasons for these observed increases and the subsequent impact on the health care needs of regional communities warrants further investigation.